Roles of Counsellors and School Administrators in Enhancing Guidance and Counselling Programmes in Some Secondary Schools Sokoto Metropolis - Ibrahim, Iklima; Ibrahim, Shehu; Sahabi, Mustapha; Abubakar, Ibrahim (Papanda Publisher, 2024)
This study evaluated the roles of teacher counsellors and school administrators in promoting guidance and counselling programmes in some selected secondary schools in the metropolis of Sokoto state. Descriptive survey design was used in this study. The participants in this study comprise 35 teacher counsellors, students, 15 school administrators, and 200 students in five selected public senior secondary schools in Sokoto metropolis. The sample size (250 respondents) of the study was obtained using simple random sampling technique. Data were collected from the participants using three sets of questionnaires. This finding showed that majority of the respondents indicated their agreements on all the stated counsellors’ and administrators’ roles in enhancing guidance and counselling programmes in secondary schools. This finding indicated that integrated guidance and counselling services in schools help to create conducive learning environment, identify and address the students’ educational, social, emotional, and behavioral needs as well as enhancing their academic performance. There is need for collaboration between teacher counsellors and school administrators to promote guidance and counselling programmes in secondary schools.